DAMPAK EXCHANGE RATE, GROWTH RATE, SUKU BUNGA DAN INFLASI TERHADAP FOREIGN DIRECT INVESTMENT (FDI) DI INDONESIA - Martadona, Ilham; Syahrial, Syahrial; Lindiawatie, Lindiawatie (Ensiklopedia of Journal, 2025)
This study analyzes the impact of exchange rate, economic growth rate, interest rate, and inflation on Foreign Direct Investment (FDI) inflows in Indonesia during the period 2018-2024. Using monthly time series data, this study adopts a Vector Autoregression (VAR) approach to understand the dynamic relationship between these variables. The results show that FDI has a unidirectional relationship with exchange rate and growth rate, where FDI inflows affect exchange rate stability and economic growth, but not vice versa. In addition, interest rates and inflation have a significant impact on changes in FDI dynamics, with exchange rate fluctuations as the key variable. This study recommends a combination of monetary and fiscal policies to create macroeconomic stability to attract foreign investment in a sustainable manner. Keywords: Foreign Direct Investment (FDI), Exchange Rate, Growth Rate, Interest Rate, Inflation, Vector Autoregression (VAR).